Financial markets and institutions - Madura, Jeff (Boston, MA : Cengage, 2021)
"This book demonstrates how today's financial institutions are integrated within financial markets. It explores the functions of the Federal Reserve System and its recent changes, major debt and equity security markets, and derivative security markets. The expanded coverage now discusses stock valuation, market microstructure strategies, and liquidity in today's financial markets. In addition, its new content introduces popular sources of funding, such as crowdfunding and students may study the management, performance, and regulatory environment of each type of financial institution" -- Publisher's website.
Includes bibliographical references and index.
Keywords: Financial institutions; Capital market; Money market; Financial institutions